Savannah blues - Andrews, Mary Kay, 1954- (HarperCollins, 2001)
Follows Eloise "Weezie" Foley, an antiques picker, as she deals with a huge estate sale, eccentric relatives, a sexy ex-boyfriend, and her ex-husband and his new girlfriend, unexpectedly discovering love is much better the second time around.